Practical workflows for monitoring saturation and pressure changes from 4D seismic data: A case study of Malay Basin - Babasafari, A.A. (Elsevier B.V., 2021)
Discrimination between fluid saturation and pore pressure-related changes using 4D seismic response is a challenging issue in reservoir studies. The main objectives of this study are the estimation of pore pressure and water saturation for baseline and monitor seismic surveys as well as determination of bypassed hydrocarbons location. To achieve this goal, we propose two practical workflows. The workflows originate from the fact that changes in pressure and saturation result in different trends on a Vp/Vs ratio versus P-Impedance cross-plot. The fact that an increase in hydrocarbon saturation results in a decrease in the Vp/Vs ratio and that an increase in pore pressure causes an increase in the Vp/Vs ratio plays a key role in this study. In this approach, after rock physics modeling and seismic data conditioning, elastic seismic inversion is performed for baseline and monitor surveys. The Bayesian probability classification technique is used to differentiate pay zones from non-pay zones which is then incorporated for prediction of fluid saturation changes. In the pore pressure prediction workflow, the Bowers equation is replaced with an empirical relationship in which a consistent match is attained between the calculated effective pressure and Vp/Vs ratio at injected water zones. Pore pressure prediction reveals noticeable anomalies around the injector wells but pressure depletion around the producers remains uncertain due to the insignificant pore pressure drop and the poor quality of seismic data near the platform area. However, at most of the producers' locations, the predicted pore pressure shows a depletion trend confirmed by the field-measured pressure. In this case study, the unswept oil and injected water areas are clearly outlined, which helps to improve sweep efficiency and update EOR scenarios. Â© 2021 Elsevier B.V.